Senescent stroma promotes prostate cancer progression: The role of miR‐210. Issue 8 (21st July 2014) - Taddei, Maria Letizia; Cavallini, Lorenzo; Comito, Giuseppina; Giannoni, Elisa; Folini, Marco; Marini, Alberto; Gandellini, Paolo; Morandi, Andrea; Pintus, Gianfranco; Raspollini, Maria Rosaria; Zaffaroni, Nadia; Chiarugi, Paola
Abstract : We focused our interest on senescent human‐derived fibroblasts in the progression of prostate cancer. Hypoxic senescent fibroblasts promote prostate cancer aggressiveness by inducing epithelial to mesenchymal transition (EMT) and by secreting energy‐rich compounds to support cancer cell growth. Hypoxic senescent fibroblasts additionally increase: i) the recruitment of monocytes and their M2‐macrophage polarization, ii) the recruitment of bone marrow‐derived endothelial precursor cells, facilitating their vasculogenic ability and iii) capillary morphogenesis, proliferation and invasion of human mature endothelial cells. In addition, we highlight that overexpression of the hypoxia‐induced miR‐210 in young fibroblasts increases their senescence‐associated features and converts them into cancer associated fibroblast (CAF)‐like cells, able to promote cancer cells EMT, to support angiogenesis and to recruit endothelial precursor cells and monocytes/macrophages. Highlights: Hypoxic senescent fibroblasts deeply sustain prostate cancer progression and modify tumor microenvironment. Senescent fibroblasts share a common gene expression profile with activated fibroblasts. miR‐210 activates fibroblasts and induces cell senescence, thus sustaining prostate cancer invasiveness.